American Prose: Mark Twain’s Social Viewpoints - kizi, Gavharoy Isroiljon; Zahro, Nurmatova (European Journal of Life Safety and Stability (2660-9630), 2021)
this article analyzes the social views, writing style, and important aspects of the great American writer Mark Twain, along with the prose genre of American literature. How he enriched the American short story with neko77 Native American humor and pointed out the way for the social novel in America. Profoundly humane Twain was above all, an uncompromising fighter for democracy and justice.